Porównania w listach emigracyjnych Joachima Lelewela pisanych do przyjaciół i znajomych - Jaros, Violetta (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2023)
The subject of this study is comparisons extracted from Joachim Lelewel’s Polish‑language émigré epistolary prose addressed to acquaintances and friends. A formal and semantic characterisation of the comparisons has been carried out, and their textual extensiveness has been identified and compared with comparisons occurring in the historiographer’s scientific subidiolect. On the basis of the formal analysis, it was established: 1) the type of comparatives in terms of their degree of fixation, 2) the manner of linking between comparandum and comparatum, 3) the array of the two members, and 4) the degree of extensionality. The semantics of the comparatives, on the other hand, made it possible to approximate the specifics of the historian’s colloquial thinking.